2010
DOI: 10.1002/pola.24060
|View full text |Cite
|
Sign up to set email alerts
|

A mixed cyclodextrin‐biphenyl thermotropic liquid crystal: Synthesis, liquid‐crystalline properties, and supramolecular organization

Abstract: A well‐defined structure liquid crystal heptakis [6‐deoxy‐6‐(1‐H‐1,2,3‐triazol‐4‐yl)(methyl)6‐(4‐methoxybiphenyl‐4′‐yloxy) hexanoyl]‐β‐cyclodextrin (H6B‐β‐CD) was synthesized from propargyl 6‐(4‐methoxybiphenyl‐4′‐yloxy) hexanoate (P6B) and heptakis (6‐deoxy‐6‐azido)‐β‐cyclodextrin ((N3)7‐β‐CD) by click reaction. The chemical structure of H6B‐β‐CD was confirmed by 1H NMR, FTIR, and MALDI‐TOF MS. The thermal stability of the compound was investigated by thermogravimetric analysis (TGA). The liquid crystalline b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“… 59 It is known that a nematic mesophase only shows a diffuse halo in a high-angle region. 60 , 61 The X-ray analysis confirmed the results of DSC and POM investigations and indicated that the obtained materials exhibited both crystalline and nematic behavior. However, detailed information about the molecular organization within the various phases at different temperatures can be obtained by X-ray diffraction measurements as a function of the temperature.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“… 59 It is known that a nematic mesophase only shows a diffuse halo in a high-angle region. 60 , 61 The X-ray analysis confirmed the results of DSC and POM investigations and indicated that the obtained materials exhibited both crystalline and nematic behavior. However, detailed information about the molecular organization within the various phases at different temperatures can be obtained by X-ray diffraction measurements as a function of the temperature.…”
Section: Resultssupporting
confidence: 70%
“…The analysis of the X-ray pattern of the pressed PLLA with thread-like texture at 25 °C (Figure , PLLA110) shows the presence of the reflections at wide angles confirming a crystalline fraction and an amorphous halo in the 2θ region 8°–26° on the flat film diffractogram, which arises from the interchain spacing and is responsible probably for N* mesophase existence . It is known that a nematic mesophase only shows a diffuse halo in a high-angle region. , The X-ray analysis confirmed the results of DSC and POM investigations and indicated that the obtained materials exhibited both crystalline and nematic behavior. However, detailed information about the molecular organization within the various phases at different temperatures can be obtained by X-ray diffraction measurements as a function of the temperature.…”
Section: Resultssupporting
confidence: 70%
“…The analysis of the X-ray pattern of pressed PLLA/RM-β-CD at 25 °C ( Figure 6 ) shows the presence of the reflections at wide angles, confirming a crystalline fraction and an amorphous halo in the 2θ region of 5–27° on the flat film diffractogram, which arises from the interchain distances, and is probably responsible for the existence of the N* mesophase [ 46 ]. It is known that a nematic mesophase only shows a diffuse halo in a high-angle region [ 47 , 48 ]. The point here is that the LC regions can cover all or only a part of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Monomers having azobenzene and biphenyl side chain groups, MAz6Ac and MBP6Ac (Scheme 1), were synthesized according to the manner reported earlier (for details see the ESI †). 10,11 The structure and purity of the monomers were identied by NMR and elemental analysis as follows.…”
Section: Methodsmentioning
confidence: 99%